Perlindungan Hukum Kreditur Terhadap Kewajiban Debitur Dengan Hak Tanggungan Dalam Relaksasi COVID-19 - Sri Resti Elviza (Faculty of Law Universitas Islam Indonesia, 2022)
The existence of coercive circumstances has prevented the debtor from fulfilling his achievements or obligations due to the current pandemic situation which has also affected the debtor's economy to decline. In this case the debtor also cannot pay for his achievements, so the loss is on the creditor or the bank that provides credit. The formulation of the problem in this research is first, how can the COVID-19 pandemic be declared as a force majeure? Second, what is the legal protection for creditors during the COVID-19 relaxation period? The research method used is normative supported by primary data. The result of this study is the legal protection given to creditors when the debtor defaults in a credit agreement with mortgage guarantees, namely the process of binding the credit agreement with mortgage guarantees then the mortgage rights are registered at the land office. Furthermore, the land office issues a Mortgage Certificate with an irah-irah of